Animus: human-embodied animals - Savulescu, Julian (Journal of medical ethics, 2024)
We review recent research to introduce human brain organoids into the brains of infant rats. This research shows these organoids integrate and function to affect behaviour in rats. We argue that this raises issues of moral status that will imminently arise and must be addressed through functional studies of these new life forms. We situate this research in the broader context of the biological revolution, arguing we already have the technological power to create fully human embodied animals. This raises profound, so far unaddressed ethical issues which call for urgent attention.